Design and analysis in educational research using Jamovi : ANOVA designs - Strunk, Kamden K.; Mwavita, Mwarumba (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book presents an integrated approach to learning about research design alongside statistical analysis concepts. Strunk and Mwavita maintain a focus on applied educational research throughout the text, with practical tips and advice on how to do high-quality quantitative research. Design and Analysis in Educational Research Using jamovi teaches research design and introductory statistical concepts, basic statistical tests and ANOVA designs, using Jamovi for analysis. This textbook is tailor-made for first-level doctoral courses in research design and analysis, and will also be of interest to graduate students in education and educational research"--
Part 1 -- Basic issues -- Basic issues in quantitative educational research -- Sampling & basic issues in research design -- Basic educational statistics ; part 2 -- Null hypothesis significance testing -- Introducing the null-hypothesis significance test -- Comparing a single sample to the population using the one-sample z-test and one-sample t-test ; part 3 -- Between-subjects designs -- Comparing two samples means : the independent samples t-test -- Independent samples t-test case studies -- Comparing more than two means using the one-way ANOVA -- One-way ANOVA case studies -- Comparing means across two independent variables : the factorial ANOVA -- Factorial ANOVA case studies ; part 4 -- within subject designs -- Comparing two within-subjects scores using the paired samples t-test -- Paired samples t-test case studies -- Comparing more than two points from within the same sample : the within-subjects ANOVA -- Within-subjects ANOVA Case Studies -- Mixed between- and within- subjects designs using the mixed ANOVA -- Mixed ANOVA case studies ; part 5 -- Considering equality in quantitative research -- Quantitative methods for social justice and equity.
Keywords: Education -- Research -- Methodology; Educational statistics; Quantitative research; PSYCHOLOGY / Research & Methodology; SOCIAL SCIENCE / Research